10x-3(x-8)=x+30

Simple and best practice solution for 10x-3(x-8)=x+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-3(x-8)=x+30 equation:


Simplifying
10x + -3(x + -8) = x + 30

Reorder the terms:
10x + -3(-8 + x) = x + 30
10x + (-8 * -3 + x * -3) = x + 30
10x + (24 + -3x) = x + 30

Reorder the terms:
24 + 10x + -3x = x + 30

Combine like terms: 10x + -3x = 7x
24 + 7x = x + 30

Reorder the terms:
24 + 7x = 30 + x

Solving
24 + 7x = 30 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
24 + 7x + -1x = 30 + x + -1x

Combine like terms: 7x + -1x = 6x
24 + 6x = 30 + x + -1x

Combine like terms: x + -1x = 0
24 + 6x = 30 + 0
24 + 6x = 30

Add '-24' to each side of the equation.
24 + -24 + 6x = 30 + -24

Combine like terms: 24 + -24 = 0
0 + 6x = 30 + -24
6x = 30 + -24

Combine like terms: 30 + -24 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| 1000*34.83= | | x-46=38 | | Ln(x+6)-ln(x-2)=5 | | 200,000*0.5337-4600= | | 8x+23=7x+17 | | 12x+4x=208 | | 17x+7=2x+17 | | 4x+2(3x-1)=x-13 | | 4x(3x-1)=68 | | 1.3(5x-8)=6(x+7.6) | | 3x+4y=53x+2y=23 | | 8x-23=7x+17 | | 6=z(10-z) | | 196x^2+49x+2=0 | | 1.054(2001)-2088= | | 2t-301/5=20 | | 3x+10=30-2x | | 5a+a=42 | | y=1.9 | | 1.054(1996)-2088= | | (1/29)=3 | | 2x-6x+3=x-5+8 | | 6x=x+288 | | 1.054(1992)-2088= | | 7x-2+9x=6x-8 | | (2x-3)=2(4x+1) | | 4(x-6)=52 | | 24=(2x)-(3x-1) | | 0.8x=0.16 | | 1.5x^2+3x-12=0 | | -3(a+5)-10(1-6a)= | | 11x+8=1x+48 |

Equations solver categories